Large anterior tibial artery pseudoaneurysm as a rare complication to vascular surgery - Eilersen, Emilie Nøddeskov (J Surg Case Rep, 2021)
A pseudoaneurysm is a rare complication to vascular reconstruction and may be limb threatening if not treated. A patient previously treated for an aneurysm of the left popliteal artery presented to our outpatient clinic with swelling and reduced active movement. Computed Tomography Angiography revealed an 8.1 cm large pseudoaneurysm of the anterior tibial artery (ATA). The pseudoaneurysm was successfully treated with an interposition vascular graft to the patent ATA. Open surgical repair was the only option with resection of the pseudoaneurysm and insertion of an interposition vascular graft with and end-to-side anastomosis. The giant ATA pseudoaneurysm was successfully treated with insertion of a new end-to-side graft anastomosis with interposition to the old patent vascular graft.